Minimally invasive KTP laser treatment of perennial allergic rhinitis: A preliminary report - Somyos Kunachak (2018)
Objective: To test the efficacy of KTP laser in controlling perennial allergic rhinitis symptoms in a minimally invasive fashion. Materials and Methods: Fifty-eight cases of refractory perennial allergic rhinitis were included in this self-controlled study. The anterior one-fourth of the inferior turbinate of one side of the nose was lased by KTP laser at 12 watts, continuous mode, the total energy per side ranging from 121 to 440 joules (mean = 252). The other side of the nose was left untreated to serve as a control. The longest follow-up time was 20 months. Results: Five patients were lost to follow-up; 53 patients were available for evaluation. For the overall result, 81% of patients reported good to excellent subjective improvement, 16.6% had fair, and 1.8% had poor subjective improvement of symptoms. The mean (± SD) degree of improvement in the treated and untreated sides was 77.1 ± 17.8% and 38.4 ± 29.4%, respectively; this was statistically significant (ρ < .001). This improvement remained at 20 months follow-up, and there were no complications. Conclusion: A single minimally invasive KTP laser treatment of perennial allergic rhinitis according to the parameters employed in this study is an effective approach resulting in moderately long-term improvement.